2008
DOI: 10.1093/ndt/gfn218
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear leukocyte injury by methylglyoxal and hydrogen peroxide: a possible pathological role for enhanced oxidative stress in chronic kidney disease

Abstract: These results indicate the combinatory effect of MGO and H(2)O(2) on PMN oxidative injury, and this pathology may be linked to enhanced oxidative stress in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…MGO is highly reactive and biologically toxic due to the formation of advanced glycation end products, protein and DNA modifications [21,22,23]. Recently, we demonstrated that MGO plays a role in the enhancement of injury to PMNs in combination with H 2 O 2 [24], which may be involved with the pathological mechanism of microinflammation in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…MGO is highly reactive and biologically toxic due to the formation of advanced glycation end products, protein and DNA modifications [21,22,23]. Recently, we demonstrated that MGO plays a role in the enhancement of injury to PMNs in combination with H 2 O 2 [24], which may be involved with the pathological mechanism of microinflammation in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methylglyoxal, an alpha-oxoaldehyde whose levels are increased in CRF, has been shown to induce apoptosis in different cell lines and to generate radicals by reacting with hydrogen peroxide, and therefore it has been postulated to act in a pivotal role in the onset of oxidative injury in CRF [36] . In light of these considerations, the evaluation of leukocyte count and function could become an easy and useful tool to verify the clinical and dialytic outcome of these hemodialysis subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists the most commonly utilized biomarkers in human and experimental models. The application of these biomarkers has now unequivocally demonstrated that acute kidney injury, chronic kidney disease, and end-stage renal disease are states of increased oxidative stress [60][61][62][63][64][65]. A more complete approach with potential promise is the utilization of multiple biomarkers from both oxidant-generating and antioxidant pathways to assess oxidative stress [60,66].…”
Section: Assessment Of Oxidative Stress-biomarker Pitfallsmentioning
confidence: 99%